2004
DOI: 10.1071/ar03173
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nutrition and management on the production and composition of milk fat and protein: a review

Abstract: The composition and functional properties of cow’s milk are of considerable importance to the dairy farmer, manufacturer, and consumer. Broadly, there are 3 options for altering the composition and/or functional properties of milk: cow nutrition and management, cow genetics, and dairy manufacturing technologies. This review considers the effects of nutrition and management on the composition and production of milk fat and protein, and the relevance of these effects to the feeding systems used in the Australian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
131
2
7

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(150 citation statements)
references
References 128 publications
10
131
2
7
Order By: Relevance
“…Feeding protein in excess has shown both positive and negative effects, but generally it increases the milk protein yield (Walker et al, 2004). This finding is in disagreement with the results in this study.…”
Section: Milk Yield and Compositioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Feeding protein in excess has shown both positive and negative effects, but generally it increases the milk protein yield (Walker et al, 2004). This finding is in disagreement with the results in this study.…”
Section: Milk Yield and Compositioncontrasting
confidence: 57%
“…After reviewing the available data, Walker et al (2004) concluded that there was no consistent effect of CP intake on milk protein concentration, except for extremely low CP intakes resulting in reduced milk protein concentrations. Feeding protein in excess has shown both positive and negative effects, but generally it increases the milk protein yield (Walker et al, 2004).…”
Section: Milk Yield and Compositionmentioning
confidence: 99%
“…When animals are genetically adapted to specific (such as organic production) or conventional farms, but only about 10% less than pasture-based conventional farms. Differences in milk yield of Holstein-Friesian cows in organic and pasturebased conventional systems respect to those producing in zero-grazing conventional systems are likely greatly related to nutrition management (Walker et al, 2004). Horan et al (2005) observed that Holstein-Friesian cows selected for high production have better milk yield under systems of high concentrate supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, protein concentrations were less variable and differences between production systems were slight. It is well assumed that fat and protein production is highly related to nutrition (Gordon & McMurray, 1979;King et al, 1990;Walker et al, 2001), depending not only on the quantity of forage and supplements but also in the composition of them (Palmquist, 1993); Walker et al, 2004). Consequently, differences in fat and protein production depend not only on the production system, but also along the year and the region.…”
Section: Discussionmentioning
confidence: 99%
“…The regulation of isomer balance is largely unknown. Nevertheless, the cis-9, trans-11 isomer is mainly generated from vaccenic acid in the mammary gland (Palmquist et al, 2005;Mosley et al, 2006), while the trans-10, cis-12 is a minor intermediate of rumen biohydrogenation (Walker et al, 2004), and is relatively unaffected by changes in the diet, except at very high levels of concentrate feeding (Chilliard et al, 2007). Therefore, future studies are necessary to determine its biological function and metabolic production routes.…”
Section: Cla Content and Compositionmentioning
confidence: 99%